2018
DOI: 10.1111/nph.15594
|View full text |Cite
|
Sign up to set email alerts
|

How flower colour signals allure bees and hummingbirds: a community‐level test of the bee avoidance hypothesis

Abstract: Summary Colour signals are the main floral trait for plant–pollinator communication. Owing to visual specificities, flower visitors exert different selective pressures on flower colour signals of plant communities. Although they evolved to attract pollinators, matching their visual sensitivity and colour preferences, floral signals may also evolve to avoid less efficient pollinators and antagonistic flower visitors. We evaluated evidence for the bee avoidance hypothesis in a Neotropical community pollinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 67 publications
(158 reference statements)
6
77
1
Order By: Relevance
“…The research shows that whilst there was no phylogenetic signal impacting upon how plants evolved their colour signals, the community‐level study in Brazil observed evidence of a significant shift in flower signals for hummingbird‐pollinated flowers towards longer wavelength reddish signals, whereas bee‐pollinated flowers more typically had short wavelength rich signals. This community‐level study provides the first detailed insights into how flower colour may potentially evolve free of phylogenetic constraints within a particular region, and thus helps explain how larger continental effects on flower colour evolution may eventuate (Shrestha et al ., ; Camargo et al .). The very interesting and highly novel finding is that whilst for the tetrachromatic colour vision of hummingbirds for either ‘bee’ or ‘bird’ visited flowers were salient and could thus be easily detected by birds against a foliage background, in the colour model for bees, the bird‐pollinated flowers were often close to the achromatic centre of colour space and thus would often be poorly detected by bees.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…The research shows that whilst there was no phylogenetic signal impacting upon how plants evolved their colour signals, the community‐level study in Brazil observed evidence of a significant shift in flower signals for hummingbird‐pollinated flowers towards longer wavelength reddish signals, whereas bee‐pollinated flowers more typically had short wavelength rich signals. This community‐level study provides the first detailed insights into how flower colour may potentially evolve free of phylogenetic constraints within a particular region, and thus helps explain how larger continental effects on flower colour evolution may eventuate (Shrestha et al ., ; Camargo et al .). The very interesting and highly novel finding is that whilst for the tetrachromatic colour vision of hummingbirds for either ‘bee’ or ‘bird’ visited flowers were salient and could thus be easily detected by birds against a foliage background, in the colour model for bees, the bird‐pollinated flowers were often close to the achromatic centre of colour space and thus would often be poorly detected by bees.…”
mentioning
confidence: 96%
“…New research by Camargo et al . in this issue of New Phytologist (pp. 1112–1122) shows that flower colouration in a community is complex, requiring a balance of presenting salient signals to attract some flower visitors, whilst minimizing how attention might be captured by other visitors that might disrupt plant reproduction.
‘This community‐level study provides the first detailed insights into how flower colour may potentially evolve free of phylogenetic constraints within a particular region …’
…”
mentioning
confidence: 99%
See 3 more Smart Citations